2017
DOI: 10.1111/jocn.13626
|View full text |Cite
|
Sign up to set email alerts
|

Exploring relationships of catheter‐associated urinary tract infection and blockage in people with long‐term indwelling urinary catheters

Abstract: Aims The aims were to describe and explore relationships among catheter problems in long-term indwelling urinary catheter users, including excess health care utilization for treating catheter problems. Background Long-term urinary catheter users experience repeated problems with catheter-related urinary tract infection (CAUTI) and blockage of the device, yet little has been reported of the patterns and relationships among relevant catheter variables. Design Secondary data analysis was conducted from a samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 43 publications
0
34
3
1
Order By: Relevance
“…Regarding the incidence of UTI, a US study described the incidence rate of UTI as 164 per 100 person-years among people with LTUC 11. The incidence rate was higher than our result of 33.8 per 100 person-years, and the difference can be explained by the different methods used to identify UTI; a questionnaire was used by interviewers in the US study, and the incidence of UTI was counted multiple times for each individual.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…Regarding the incidence of UTI, a US study described the incidence rate of UTI as 164 per 100 person-years among people with LTUC 11. The incidence rate was higher than our result of 33.8 per 100 person-years, and the difference can be explained by the different methods used to identify UTI; a questionnaire was used by interviewers in the US study, and the incidence of UTI was counted multiple times for each individual.…”
Section: Discussioncontrasting
confidence: 69%
“…Potential harms associated with urinary catheterisation include urinary tract infection (UTI) 9 10. A US study reported that UTI occurred in 50% of people with LTUC in the community 11. However, this study did not include a comparison group of people without LTUC, and the relative risk of UTI in people with LTUC was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…Early ureter extraction caused a reduction in the risk of urinary tract infection42; however, this study found that there was no significant difference between ERAS and the control group. Sensitivity analysis showed that by excluding Kim’s study,33 the ERAS group had a lower risk of urinary tract infection than the control group.…”
Section: Discussioncontrasting
confidence: 68%
“…CAUTI have also been associated with bladder spasms ( 25 ). Treating the CAUTI with antibiotics may reduce the spasms, however in some patients the spasms will persist.…”
Section: Complications Of Long Term Catheterizationmentioning
confidence: 99%